U.S. Food System Working Conditions as an Issue of Food Safety: Key Stakeholder Perspectives for Setting the Policy Agenda. (February 2017) - Clayton, Megan L.; Smith, Katherine C.; Pollack, Keshia M.; Neff, Roni A.; Rutkow, Lainie
Food workers' health and hygiene are common pathways to foodborne disease outbreaks. Improving food system jobs is important to food safety because working conditions impact workers' health, hygiene, and safe food handling. Stakeholders from key industries have advanced working conditions as an issue of public safety in the United States. Yet, for the food industry, stakeholder engagement with this topic is seemingly limited. To understand this lack of action, we interviewed key informants from organizations recognized for their agenda-setting role on food-worker issues. Findings suggest that participants recognize the work standards/food safety connection, yet perceived barriers limit adoption of a food safety frame, including more pressing priorities (e.g., occupational safety); poor fit with organizational strategies and mission; and questionable utility, including potential negative consequences. Using these findings, we consider how public health advocates may connect food working conditions to food and public safety and elevate it to the public policy agenda.